Factors Determining the Purchase Intention of Bank Services in the Republic of Yemen - Al Qasa, Khaled Mohammed Ahmed (2013)
The issue of motivating consumers to use the banking system was solved in developed countries and in some Middle Eastern countries. However, it is still unpredictable in Yemen where the majority of the people do not use banking services to facilitate their financial needs. Therefore, it shapes a real problem and negatively impacted the Yemeni economy. This research project aimed to provide better awareness of the variables that might affect people to use the Yemeni banking system by applying the theory of reasoned action. This study is cross-sectional, 850 questionnaires were distributed to part time university students. Multiple regression analysis was conducted to determine the contribution of independent variables in predicting behavioral intention, the dependent variable. Moreover, hierarchical regressions were used to test the effect of trust as a moderator variable. Eight variables of attitude and subjective norm were significantly and positively influence university student's behavioral intention to use banking services namely, attitude toward bank usage, attitude towards banking services, attitude toward service quality, attitude towards banking legal framework, social influence, recommendation by others on bank services, and bank advertisement. On the other hand, cultural belief was significant but in the negative direction. As well as, student’s trust had a statistically moderating effect with only three out of eight variables on the behavioral intention namely attitude toward bank usage, recommendation by others on bank services, cultural belief. The study had a significant contribution to the academic understanding of consumer's behavioral intention in Yemen, which might guide bankers and policy makers to use the right strategy in order to attract more consumers to use the banking system.